Menilik Perkembangan Perintisan Wirausaha Peternakan Ayam Petelur melalui Program Matching Grant di Desa Keramajaya, Narmada, Lombok Barat - Tamzil, Mohammad Hasil; Indarsih, Budi; Septian, Gde Nano (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This activity aims to evaluate the development of the pioneering project of egg-laying chicken farming in Keramajaya Village, Narmada District, West Lombok Regency. This project is part of the Matching Grant program which is a collaboration between Gadjah Mada University, Yogyakarta and Mataram University. Monitoring activities are carried out through direct evaluation of the condition of the cage, feeding system and provision, livestock development, and egg production. Data collection is carried out through structured interviews with group members using interview guides, as well as direct observation at the farm location. In addition, socio-institutional aspects are also studied, which include: (1) member participation, (2) group performance, and (3) business sustainability. The evaluation results show that the egg-laying chicken farming business is running well. All group members show solidarity and togetherness, especially in decision-making related to business direction. During the two years of project implementation, the chicken population increased from 150 to 440, which was obtained from the profits from the sale of eggs and culled chickens. It is concluded that the pioneering project of egg-laying chicken farming in Keramajaya Village has good prospects and has the potential to develop into an independent and sustainable group farming business.